Thermal performance of cylindrical battery module with both axial and radial thermal paths: Numerical simulation and thermal resistance network analysis. (May 2022) - Zhu, Jiajun; Zhang, Hengyun; Wu, Guoping; Zhu, Shunliang; Liu, Wei
Highlights: Parametric effects are investigated by the numerical simulation for the representative battery with surrounding thermal structure. The maximum temperature and temperature difference are mostly affected by thermal column and coaxial tube but not by thickness of diffusion plate and shape of column. Analytical thermal resistance model with correction coefficient δ is obtained for representative battery and module with cold plate. Deviations in the maximum temperature and temperature difference between analytical and numerical results are below 6.5%, demonstrating validity of analytical solution. Analytical solution is applicable for both isotropic and anisotropic battery thermal models available in literature. Abstract: In this paper, the thermal performance of a cylindrical battery module with axial-radial thermal paths is investigated by both numerical simulation and analytical thermal resistance network analysis. The 7 × 7 cylindrical lithium-ion batteries are arranged orthogonally in the module, with their base surface dissipating heat to the cold plate through bottom electrical insulation layer. The upper part of the battery is connected to the cold plate by the surrounding coaxial tube, thermal diffusion plate and thermal column, thus forming the cooperative cooling thermal structure in both axial and radial directions. The temperature distribution in the battery module is first analyzed by numerical modeling, and then the structural parameters are investigated including the spacing between the adjacent battery centers, the cross-sectional shape and area of thermal column, the thickness of thermal diffusion plate, the height of thermal diffusion plate and the length of coaxial tube. It is found that the effect of the cross-sectional area of the thermal column surpasses the other affecting parameters. For the thermal resistance analysis, the representative unit cell (RUC) with the corresponding thermal structure is examined and the analytical model of the battery module with internal heat source is established based on the criteria of minimized battery temperature gradient. The comparison between analytical solution and numerical simulation shows that the maximum relative deviations of battery temperature and temperature difference are 4.6% and 6.5%, respectively, validating the effectiveness of the analytical results. The present analytical method can be a useful tool in the fast analysis of the battery thermal designs with acceptable accuracy validated by real and mock-up battery experimental tests. Graphical abstract : Image, graphical abstract